USING SCAFFOLDING IN CLIL TO IMPROVE MATERIAL COMPREHENSION - Tastanov, M.G.; Kurmangaliyeva, А.А. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
The article examines the impact of the scaffolding method on learning subjects in English within the CLIL framework. The study analyses the key principles of pedagogical support, considers different types of scaffolding, and evaluates its effect on students’ academic performance and motivation. The findings confirm that scaffolded methods enhance comprehension, foster critical thinking, and reduce cognitive load. The research highlights the need for a flexible approach to scaffolding, depending on students’ proficiency levels.
Keywords: scaffolding; CLIL; language support; cognitive load; academic success; bilingual education; critical thinking